The metabolomics changes in epididymal lumen fluid of CABS1 deficient male mice potentially contribute to sperm deformity - Zhao, Xiuling; Nie, Junyu; Zhou, Wenwen; Zeng, Xuhui; Sun, Xiaoli (Frontiers in Endocrinology, 2024)
Epididymal lumen fluids provides a stable microenvironment for sperm maturation. Ca2+ binding protein CABS1 is known to maintain structural integrity of mouse sperm flagella during epididymal transit of sperm. Besides, CABS1 was reported to contain anti-inflammatory peptide sequences and be present in both human saliva and plasma. However, little is known about the role of CABS1 in regulation of the microenvironment of epididymal lumen fluids. To further confirm the role of CABS1 in epididymis, we identified the expression of CABS1 in epididymal lumen fluids. Moreover, high performance liquid chromatography, coupled with tandem mass spectrometry technique was used to analyze the metabolic profiles and in vivo microperfusion of the cauda epididymis and inductively coupled plasma mass spectrometry (ICP-MS) assays was used to detect the concentration of metal ion of mouse cauda epididymal lumen fluids in CABS1 deficient and normal mice. The results showed that CABS1 is present in epididymal lumen fluids, and the concentration of calcium in epididymal lumen fluids is not changed in Cabs1-/- male mice. Among 34 differential metabolites identified in cauda epididymis, 21 were significantly upregulated while 13 were significantly downregulated in KO cauda epididymis. Pathway analysis identified pyrimidine metabolism, inositol phosphate metabolism, arachidonic acid metabolism, purine metabolism and histidine metabolism as relevant pathways in cauda epididymis. The perturbations of mitochondrial dysfunction and inflammation may be the crucial reason for the poor performance of Cabs1-/- sperm.